The Analysis of Language Politeness Used by Famous Child (Range 5-13 Years) - Alfiyatu Nuuriyyah Aa Minatul Imaamah; Rosita Ambarwati (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
Politeness has an important role in communication. It is used not only by adults, but also by young people. This study aims to identify and describe politeness use among famous children in the video of"Catatan Si Bocil". This study was based on the theory of Leech. The research approach used in this research is qualitative research. The research data is in the form of conversations between two famous children in TV content uploaded on Youtube. The data source is a YouTube video showing two famous children communicating with each other, then written in a conversational form. The technique of collecting the data was domentation. The results of the study show that there are 6 politeness maxims used by young people in activities. The maxims consist of 1 (one) data maxim of wisdom, 1 (one) data maxim of generosity, 4 (four) data maxims of appreciation, 2 (two) data maxims of modesty, 3 (three) data maxims of consultation. and 1 (one) data of sympathy maxim. Based on research data, the most dominant maxim is the maxim of appreciation.